Impact of Training Program on Recent Innovations in Oncology Among Nursing Professionals - Davinder Kaur; Poonam Thakur; Ravinder Kaur (International Journal of Oncological Nursing and Practices, 2025)
Introduction: In recent years, there have been significant advancements and trends in the field of oncology treatment in India. This study aimed to evaluate impact of training program on knowledge regarding recent innovations in oncology among nursing professionals. After ethical approval, a pre-experimental, one group pretest- post-test design was used to conduct this research at anursing college of Punjab. Methods: The sample was selected using the total enumerative sampling technique. Sample size calculation was not done as it was one day training program and all participants who attended the program and also meeting the criteria of inclusion were enrolled. 80 nursing professionals, out of which 39% students of BSc Nursing 3rd year, 25% teachers and 30% nursing officers were enrolled. Self-structured questionnaire was prepared and got validated by experts and reliability was checked. It had 30 multiple-choice questions related to the incidence, recent advancements in the diagnosis, and treatment of cancer. After pretest, one day training was imparted regarding recent advances in oncology and hands on practice done on stoma care. Overview of global and Indian scenario of cancer, recent advances in molecular diagnostic oncology, current perspectives and new challenges, recent advances in tumor-targeting and impact of chemotherapeutic drugs, benefits of proto and radiation therapy, targeted immunotherapy in oncology, complementary and alternative medicine, chemotherapy, nurses’ role and drug administrative errors stoma care and oncology nursing perspectives was discussed. Post-test was taken on the same day after the training. Data was analyzed for descriptive and inferential statistics by SPSS version 21. R software (Ross Ihaka and Robert Gentleman software) has been used for item analysis. Results: The study results showed that the pre-test mean knowledge score was 17.02, while the post-test mean knowledge score was 19.15. There was a highly significant (p<0.0001) improvement in the nurses' knowledge after the training program. Conclusion: This study concluded that teaching program was proved to be a useful intervention for nurses to enhance their knowledge regarding recent innovations in oncology for comprehensive patient care.
Keywords: Challenges; Impact; Nursing; oncology; professionals; recent innovations; training program